The Effect of Parental Attachment on Online Learning for Children with Mental Reterdation at Special Schools - Farhana, Surya; Kasiyati, Kasiyati (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2022)
During the COVID-19 period, the Ministry of Education and Culture has determined that learning is carried out from home called online learning. This study is to determine the effect of parental attachment on online learning for children with mental reterdation in SLB East Jakarta area 1.This study uses a quantitative approach with descriptive type. Data collection by questionnaire to 251 respondents whose data results were processed using SPSS. The F test results show the F table value of 3.88. The calculated F value is 36.909 bigger F table 3.88 and that all independent variables, namely parental attachment , simultaneously have a significant effect on the dependent variable, namely online learning. The result of T count is 6.075 bigger 1.652 from T table which means it has a positive effect. The results of partial hypothesis testing indicate that parental attachment has a significant effect on online learning.